Narratives on Terrorism in Iraq through the Arabic Novels of Yā Maryam, Al-Kāfirah, and Frankenstein fī Baghdād - Yoyo, Yoyo; Hussin, Mohamad; Zaini, Abdul Razif; Sukiman, Uki; Yunianti, Fitria Sari (Journal of Al-Tamaddun, 2025)
To date, the narratives on terrorism carried out by some scholars tend to use a monolithic perspective that relates the acts of terrorism as a manifestation of the dogmatic teaching of a particular belief. Massive narratives on terrorism through this monolithic perspective reached their momentum after the infamous 9/11 terrorist attack. Therefore, there is a need to study terrorism through Arabic novels through a more genuine narrative. This paper aims to analyze Arabic novels on terrorism in the Iraqi context. The author investigates how Arab novelists narrate terrorism in their literary works. The novels studied here are 1) Yā Maryam by [O…Maryam] Sinan Antoon (2012), 2) Al-Kāfirah [The Disbelieve, fem.] by Ali Badr (2015), and Frankenstein fī Baghdād [Frankenstein in Baghdad] by Ahmad Sa'dawi (2013). The study found that the three novels represent the same narratives on terrorism: terrorism is detrimental and destroys social lives. The acts of terrorism do not represent any true religious belief, but it was a deviated one coming from misinterpretation of religious doctrines.